Health related quality of life of Dutch children: psychometric properties of the PedsQL in the Netherlands - Koopman Hendrik M; Detmar Symone B; Haentjens Marleen M; Engelen Vivian; Grootenhuis Martha A (BMC, 2009)
Abstract Background Knowledge about psychometric properties of the Pediatric Quality of Life Inventory (PedsQL) in the Netherlands is limited and Dutch reference data are lacking. Aim of the current study is to collect Dutch reference data of the PedsQL and subsequently assess reliability, socio-demographic within-group differences and construct validity. Methods In this study the PedsQL was administered to Dutch children aged 5 to 18 years. A socio-demographic questionnaire was completed as well. The sample consisted of three age groups: 5-7 years (parent proxy report), 8-12 years and 13-18 years (child self report). Analysis was performed with SPSS 16.0.2. A reliability analysis was done using Cronbach's alpha coefficient. Socio-demographic within-group differences were assessed by means of an ANOVA with post hoc Bonferroni correction and t-tests. Subsequently, construct validity was determined by t-tests and effect sizes. Results For 496 children PedsQL reference data were collected. PedsQL total scores were 84.18 (group 5-7), 82.11 (group 8-12) and 82.24 (group 13-18). Internal consistency coefficients ranged from .53 to .85. Socio-demographic within-group differences demonstrated that, in group 8-12, children of parents born in the Netherlands had significantly lower scores on several PedsQL subscales, compared to children of parents born in another country. With respect to construct validity, healthy children of group 5-7 and 13-18 scored significantly higher than children with a chronic health condition on all subscales, except for emotional functioning. In group 5-7, the PedsQL total score for healthy children was 85.31, whereas the same age group with a chronic health condition scored 78.80. Effect sizes in this group varied from 0.58 to 0.88. With respect to group 13-18, healthy children obtained a PedsQL total score of 83.14 and children suffering from a chronic health condition 77.09. Effect sizes in this group varied from 0.45 to 0.67. No significant differences were found in group 8-12 regarding health. Conclusion The Dutch version of the PedsQL has adequate psychometric properties and can be used as a health related quality of life instrument in paediatric research in the Netherlands.